Biochemical features and modulation of digestive enzymes by environmental temperature in the greater amberjack, Seriola dumerili - Navarro-Guillén, Carmen; Yúfera, Manuel; Perera, Erick (Frontiers in Marine Science, 2022)
The study of fish digestive biochemistry is essential to understand factors that affect the net efficiency of food transformation and growth, and therefore aquaculture profitability. The aim of the present study was to assess the activity and functional characteristics of key digestive enzymes in juveniles of greater amberjack (Seriola dumerili), as well as the possible modulation of their relative importance by water temperature. For that, a combination of biochemical assays and substrate-SDS-PAGE were used. Under physiological conditions pepsin activity was negligible. Chymotrypsin was the most active enzyme in the digestive tract of the greater amberjack, while lipase was the enzyme with lower activity, though both enzymes in addition to trypsin were responsive to water temperature as revealed by discriminant analysis. Seriola dumerili showed to have pH-sensitive and, except for chymotrypsin, thermally robust proteases. Inhibition assays showed the major importance of serine proteases and revealed inverse trypsin and chymotrypsin responses to environmental temperature, with higher trypsin contribution in 26°C-fish while higher chymotrypsin contribution in 18°C-fish. Zymograms revealed three isotrypsin and three isochymotrypsin enzymes, with no variation in the presence of particular isoforms among rearing temperatures. However, they confirmed the role of chymotrypsin activity in providing digestive plasticity, with one of the isoforms being more active at lower temperatures. Thus, results indicate that variation in the relative contribution of chymotrypsin isoenzymes to a particular environmental temperature occurs due to different physic-chemical features of isoforms as a source of functional flexibility. This study assessed for the first time the effects of rearing temperature on greater amberjack digestive enzymes, increasing the knowledge on its digestive biochemistry, and aiding in the improvement of management practices for this species industrialization.